2015
DOI: 10.3390/md13041847
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Exopolysaccharides from Paenibacillus spp.: Production, Isolation, Structure, and Bioactivities

Abstract: This review provides a comprehensive summary of the most recent developments of various aspects (i.e., production, purification, structure, and bioactivity) of the exopolysaccharides (EPSs) from Paenibacillus spp. For the production, in particular, squid pen waste was first utilized successfully to produce a high yield of inexpensive EPSs from Paenibacillus sp. TKU023 and P. macerans TKU029. In addition, this technology for EPS production is prevailing because it is more environmentally friendly. The Paenibaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 64 publications
3
60
0
3
Order By: Relevance
“…By contrast, Huang et al [34] reported the inhibition rate of beta-(1-3) glucan isolated from Poria cocos mycelia on Sarcoma 180 as less than 10%. The antitumor activities of beta-glucans are determined by their molecular weight and solubility in water [35], which may explain why the antitumor activity of beta-glucan from P. polymyxa JB115 did not increase to a significant extent at higher concentrations [35,36]. Antitumor activity of beta-glucans has been suggested to exhibit various physiological activities depending on the relative composition of water-soluble beta-glucan, insoluble beta-glucan, hetero-beta-glucan, and beta-glucan-protein complex [34,36].…”
Section: Cell Linementioning
confidence: 98%
See 1 more Smart Citation
“…By contrast, Huang et al [34] reported the inhibition rate of beta-(1-3) glucan isolated from Poria cocos mycelia on Sarcoma 180 as less than 10%. The antitumor activities of beta-glucans are determined by their molecular weight and solubility in water [35], which may explain why the antitumor activity of beta-glucan from P. polymyxa JB115 did not increase to a significant extent at higher concentrations [35,36]. Antitumor activity of beta-glucans has been suggested to exhibit various physiological activities depending on the relative composition of water-soluble beta-glucan, insoluble beta-glucan, hetero-beta-glucan, and beta-glucan-protein complex [34,36].…”
Section: Cell Linementioning
confidence: 98%
“…The antitumor activities of beta-glucans are determined by their molecular weight and solubility in water [35], which may explain why the antitumor activity of beta-glucan from P. polymyxa JB115 did not increase to a significant extent at higher concentrations [35,36]. Antitumor activity of beta-glucans has been suggested to exhibit various physiological activities depending on the relative composition of water-soluble beta-glucan, insoluble beta-glucan, hetero-beta-glucan, and beta-glucan-protein complex [34,36]. Macrophages play many critical functions in the body defense against neoplasm and beta-glucans are known to be an immunostimulation agents [37].…”
Section: Cell Linementioning
confidence: 98%
“…Paenibacillus продуцирует широкий спектр экзополисахаридов (ЭПС) с различны-ми физиологическими и биотехнологическими функциями, что способствует их активному использованию в различных промышленных процессах и сельском хозяйстве [4,12]. Также данные биополимеры являются важными ме-таболитами, которые играют ключевую роль в растительно-бактериальных взаимодействиях [6,13].…”
Section: Effect Of Exopolysaccharides Of the Bacteriumunclassified
“…2) наиболее существенная реакция на на-личие или отсутствие света наблюдается в от-ношении колеоптиля и эпикотиля проростков, что, очевидно [5,12], связано с наличием в них различных групп сенсорных пигментов;…”
unclassified
“…Moreover, a number of other important roles of microbial exopolysaccharides have been reported recently (Liang and Wang, 2015). Various exopolysaccharides have been found to protect microorganisms from dehydration, phagocytosis, predation, bacteriophage attack, and from the adversary effects of antibiotics and toxic compounds (Roberts, 1996).…”
Section: Industrial and Pharmacological Applications Of Exopolysacchamentioning
confidence: 99%